Platonism : Ficino to Foucault - Rees, Valery, 1947-; Corrias, Anna; Crasta, Francesca Maria; Follesa, Laura; Giglioni, Guido (Brill's studies in intellectual history, 2021)
"The sixteen essays in this volume trace the development of Platonism in the history of Western thought, starting with the revival of the Platonic tradition in the early modern period that followed the rediscovery and translation of important Greek texts. Special attention is devoted to Marsilio Ficino's translations and commentaries; to the relationship between Platonism and Christianity; to the influence of Platonic metaphysics on the mystical tradition - in particular on Jacob Böhme and Emanuel Swedenborg; to the impact of idealism on the hermeneutical criticism of traditional philosophical categories and to the ways in which the so-called 'Critique of Modernity' promoted a new reading of the Platonic dialogues. The emphasis throughout is on demonstrating the theoretical and historical continuity of Platonism over the centuries"--